Is "Few" Always Less than Expected?: The Influence of Story Context on Readers' Interpretation of Natural Language Quantifiers. Issue 8 (17th November 2019) - Upadhyay, Sri Siddhi N.; Houghton, Kenneth J.; Klin, Celia M.
ABSTRACT: After reading, few of the juniors were accepted, focus is on the students not accepted, the complement set. According to the Presupposition Denial Account, negative quantifiers, such as few, convey a denial of expectation, or shortfall, which leads to complement set focus. In six experiments, we explored the role of the passage context on the comprehension of negative quantifiers. We examined reading times on an anaphoric reference ( the students …) to negatively quantified statements. When the story context introduced an expectation for a small quantity ( most years, a lot of weak students apply ), few was consistent with readers' expectations, and did not indicate that there was shortfall. Despite this, after the negative quantifier, focus on the complement set was not reduced. In contrast, when the story context introduced the expectation for a small quantity, there was increased focus on the reference set (the students accepted). The polarity of natural language quantifiers interacts with the discourse context to influence the comprehension of negative quantifiers.